Özlem Günyol & Mustafa Kunt Sandra Kuhne Regine Müller-Waldeck Martin Pfeifle Martin Wöhrl. - Lorenz, Ulrike; Hose, Gregor; Jansen, Gregor; Kleine, Rasmus; Köllhofer, Thomas (Mannheim : Kunsthalle Mannheim Wienand Verlag Köln, 2009)
Günyol, Özlem ; Kunt, Mustafa ; Kuhne, Sandra ; Müller-Waldeck, Regine ; Pfeifle, Martin ; Wöhrl, Martin
Exhibition. Hector Förderpreis 2009. Mannheim. Kunsthalle Mannheim. 2009-12-05. 2010-02-28
biog., tent. p. 74-78
boek
Keywords: Günyol, Özlem; Kunt, Mustafa; Kuhne, Sandra; Müller-Waldeck, Regine; Pfeifle, Martin; Wöhrl, Martin